Business Sustainability of Food and Beverage Companies in The Asean Capital Market: The Role of Risk Management to Enhance Financial Resilience - Makhnun, Intan Jauharul; Yuhertiana, Indrawati; Sundari, Siti (Green Publisher Indonesia, 2025)
The purpose of this study is to analyze the effect of sustainability reports on financial resilience in food and beverage companies in capital market of ASEAN countries and analyze the role of Enterprise Risk Management in modifying effect of the relationship. The index used as a sustainability report guideline in this study is based on Global Reporting Initiative (GRI) 2021. Meanwhile, the index used to measure Enterprise Risk Management is using COSO - ERM. The population of this study are food and beverage industry companies listed on the stock exchange of each ASEAN country in 2022-2023. Companies that become samples are selected using purposive sampling method with certain criteria. The type of data used is secondary data. The results showed that sustainability reports had no effect on Economic Value Added, and Enterprise Risk Management had no role in moderating effect of sustainability reports on Economic Value Added. Although ERM is designed to reduce risk and increase stability, this study suggests that ERM may not be sufficiently integrated with sustainability initiatives to influence financial resilience as measured by EVA. Sustainability initiatives reported in the SR are more oriented towards long-term impacts related to environmental, social, and governance (ESG). Due to this difference in focus, ERM is often not directly involved in managing or measuring the effectiveness of sustainability initiatives, leading to a lack of synergy between two approaches. The implications of this study can help companies to pay more attention to sustainability practices and strengthen risk management to improve financial resilience.